Visible‐Light‐Driven Competitive Stereo‐ and Regioisomerization of (E)‐β‐Nitroenones. Issue 9 (10th June 2021) - Raviola, Carlotta; Carrera, Cristina; Serra, Massimo; Palmieri, Alessandro; Lupidi, Gabriele; Maestri, Giovanni; Protti, Stefano
Abstract: A combined experimental and computational investigation of the photoreactivity of ( E )‐β‐nitroenones pointed out the occurrence of competitive pathways namely stereoisomerisation to ( E )‐β‐nitroenones and deconjugation to β‐nitro‐β, γ‐enones. Both processes are generated from the triplet excited state of the starting substrates. Abstract : A split decision : The photoreactivity of ( E )‐β‐nitroenones was investigated by a combined computational/experimental approach, that revealed the presence of two competitive pathways namely stereoisomerisation to ( E )‐β‐nitroenones and deconjugation to β‐nitro‐β, γ‐enones, both of them arising from the triplet excited state of the substrates.